2023
DOI: 10.1039/d3dt00365e
|View full text |Cite
|
Sign up to set email alerts
|

Pore-forming mechanisms and sodium-ion-storage performances in a porous Na3V2(PO4)3/C composite cathode

Abstract: Na3V2(PO4)3 (NVP) is regarded as one of the most promising cathode materials for sodium ion batteries (SIBs). However, it suffers from dense bulk structure and low intrinsic electronic conductivity which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The cathode exhibited a reversible capacity of 109.8 mAh/g at 5 C and maintained 87.6% stability after 400 cycles (at 5 C). The synergistic heterojunction enhanced the electron mobility by reducing the scattering and collision caused by anion dopants [41].…”
Section: Nvp Cathodes By Sol-gel Methodsmentioning
confidence: 99%
“…The cathode exhibited a reversible capacity of 109.8 mAh/g at 5 C and maintained 87.6% stability after 400 cycles (at 5 C). The synergistic heterojunction enhanced the electron mobility by reducing the scattering and collision caused by anion dopants [41].…”
Section: Nvp Cathodes By Sol-gel Methodsmentioning
confidence: 99%
“…[166] However, the high cost of rGO is contrary to the main advantage of low-cost SIBs, so some other novel carbon sources such MWCNTs, carbon sheets and carbon fibers are employed by various researchers. [167,168] For instance, Su et al [169] synthesized hierarchical flower-like Na 3 V 2 (PO 4 ) 3 /C microspheres coated with a dense and highly conductive carbon layer derived from polyvinylpyrrolidone (PVP) addition via solvothermal method and subsequent annealing. The Na 3 V 2 (PO 4 ) 3 /C cathode demonstrated exceptional cycling stability maintaining a reversible capacity of 84.3 mAh g −1 over 10 000 cycles at 40 C. Li et al [21] reported dual carbon decorated heterostructure Na 3 V 2 O 2 (PO 4 ) 2 F@C/CNFs via solvothermal synthesis route with homogenous amorphous carbon layer wrapping NVOPF particles coupled with graphitized CNFs externally followed by post annealing treatment (Figure 9e-g).…”
Section: Surface Coatingmentioning
confidence: 99%
“…[ 166 ] However, the high cost of rGO is contrary to the main advantage of low‐cost SIBs, so some other novel carbon sources such MWCNTs, carbon sheets and carbon fibers are employed by various researchers. [ 167,168 ] For instance, Su et al. [ 169 ] synthesized hierarchical flower‐like Na 3 V 2 (PO 4 ) 3 /C microspheres coated with a dense and highly conductive carbon layer derived from polyvinylpyrrolidone (PVP) addition via solvothermal method and subsequent annealing.…”
Section: Strategies For Improving High‐performance Phosphate‐based Po...mentioning
confidence: 99%
“…[5] To obtain a sufficient conductivity of the cathodes, NVP/carbon composite coatings are applied. [6][7][8] The performance of the cell strongly depends on effective properties of the composite material at the nano-scale, which-in turnare influenced by the spatial distribution of the constituents of this composite material. Optimizing these electrode materials requires a comprehensive understanding of relationships between parameters of the synthesis process, the morphology of the composite material, and the corresponding effective properties.…”
Section: Introductionmentioning
confidence: 99%
“…The main benefit of this material arises from its high energy density, cycle stability, and rate capability [5] . To obtain a sufficient conductivity of the cathodes, NVP/carbon composite coatings are applied [6–8] . The performance of the cell strongly depends on effective properties of the composite material at the nano‐scale, which–in turn–are influenced by the spatial distribution of the constituents of this composite material.…”
Section: Introductionmentioning
confidence: 99%